The effect of Vitamin E on growth, survival and hepatopancreas structure of the Argentine red shrimp Pleoticus muelleri Bate (Crustacea, Penaeidae) - Fernandez Gimenez, Analia Veronica (2004)
Two trials were conducted to evaluate the growth, survival and hepatopancreas histology of the Argentine red shrimp Pleoticus muelleri (Bate, 1888) fed different levels of vitamin E and butylated hydroxytoluene (BHT) in a semipurified diet. The diets contained 0, 100, 600 or 1500 mg vitamin E kg−1 and 16 mg BHT kg−1 diet (trial 1) and 0, 1250, 1500, 1750 or 2000 mg vitamin E kg−1 diet, squid mantle and vitamin-free diet as a control (trial 2). After 30 days (trial 1), survival ranged between 43% and 64%, and the percentage weight gain of the shrimp varied from 22% to 31% with no significant differences among treatments (P<0.05). After 40 days (trial 2), survival of shrimp fed the diet with no vitamin E and squid mantle was significantly lower (62%) than the other treatment (86–90%). Shrimp fed diets containing vitamin E from 1250 to 1750 mg kg−1 exhibited increased weight gain (34–65%); however, a significant difference was observed for shrimp fed the diet containing 2000 mg kg−1. Histological results yielded differences among treatments. In shrimp fed 1750 mg kg−1 of vitamin E, the functional morphology of the organ was normal, with abundant secretion in the tubules. Signs of malnourishment such as cellular and nuclear retraction, desquamation of cells and hipertrofia, were evident in the hepatopancreas of shrimp fed the other diets. The results indicate that optimal vitamin E requirement for P. muelleri under the present experimental conditions appears to be approximately 1750 mg vitamin E kg−1 diet.